Longitudinal associations of meaning in life and psychosocial adjustment to the COVID‐19 outbreak in China - Lin, Li (British journal of health psychology, 2021)
Objective Literature suggests that ‘meaning in life’ may be a mental strength that enables individuals to function healthily and adaptively in the face of stress events. Therefore, this study aims to examine the longitudinal associations between meaning in life and psychosocial adjustment to the COVID‐19 outbreak among Chinese people. Methods A prospective design was adopted. 154 Chinese college students (Mean age = 20.41 ± 1.45 years) completed two waves of the assessment. Participants reported their meaning in life before the outbreak (Time 1) and their psychosocial adjustment 7 weeks later after the outbreak had occurred (Time 2). Results Participants’ meaning in life at Time 1 was positively related to life satisfaction and negatively related to depression, anxiety, stress, and negative emotions at Time 2. Additionally, levels of meaning in life at Time 1 were positively associated to COVID‐19‐related behavioural engagement – prosocial behaviour and information addiction at Time 2. Individuals’ perceptions of the outbreak and status of self‐quarantine did not moderate these relationships. Conclusion Findings suggest that individuals’ prior level of meaning in life may help them maintain a healthy psychosocial adjustment during disease outbreak, though cautions regarding the possibility to render an addiction to information about the outbreak are warranted.